PENGARUH PROFITABILITAS, LIKUIDITAS, PERTUMBUHAN ASET, UKURAN PERUSAHAAN, DAN KEBIJAKAN DEVIDEN TERHADAP STRUKTUR MODAL (STUDI PADA PERUSAHAAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017) - Doni Dharmawan Anjasmara Putra, 15.05.52.0058; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the Effect of Profitability, Liquidity, Asset Growth, Company Size, and Dividend Policy on Capital Structure (Study on Real Estate Companies Listed on the Indonesia Stock Exchange 2014-2017). The sampling technique in this study used a purposive sampling technique. The data used is secondary data obtained from the Indonesia Stock Exchange. The data analysis method used in this study is the analysis of Multiple Linear Regression and assisted by SPSS version 22 statistical test. The results of this study indicate that Profitability has a significant effect on Capital Structure, Liquidity has a significant effect on Capital Structure, Asset Growth has no significant effect on Capital Structure, Company Size has no significant effect on Capital Structure, and Dividend Policy has no significant effect on Capital Structure.